The perceived value of book borrowing services is stationary in the time of Covid-19: Empirical evidence from the Municipal Library in Prague - Stejskal, Jan; Zapletal, David; Prokop, Viktor (SAGE Publications, 2023)
Public libraries represent a specific sector of public service provision, where library management is limited in its ability to influence consumers' perceptions of the value of borrowed books. This study expands previous research on consumers' perceived value and its measurement and focuses on the nature of the data examined, which has not yet received much attention. We fill this research gap and examine whether the perceived value of book borrowing services remains stationary over time by considering a sample of readers from the Municipal Library in Prague, Czech Republic. Moreover, we analyse whether the Covid-19 pandemic has affected the perceived value of book borrowing services. Our results contribute to the discussion an important finding that consumers' perceptions of book borrowing services are stable and do not change over time. Interestingly, we also find that the Covid-19 pandemic has not led to a change in consumers' perceived value. This study thus creates both theoretical and practical contributions and leads to the definition of several practical implications for managers of (public) library organisations. JEL L86, H39, H44
Vnímaná hodnota služeb půjčování knih je v době Covid-19 neměnná: Empirické důkazy z Městské knihovny v Praze
Keywords: contingent valuation; covid-19; perceived value; public library; kontingenční oceňování; covid-19; vnímaná hodnota; veřejná knihovna